Arranjos institucionais, custo da dívida pública e equilíbrio fiscal: A despesa "ausente" e os limites do ajuste estrutural - Luís Carlos Garcia de Magalh\~aes; Carla Rodrigues Costa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The issue of fiscal imbalance has become central to the current economic debate. A diagnostic Brazilian fiscal problem emphasizes that the rise in primary expenditure stems from "structural" factors, due to the growth of social security spending and social programs, resulting from the 1988 Constitution. The projected growth of these primary expenditures would make the trajectory untenable of the public debt / GDP indicator. Therefore, it would be necessary to adopt policies that limit the growth of primary expenditures of the federal public sector, especially social security expenditures and social programs. The objective of this study is to critically discuss this diagnosis, emphasizing that the high expenditure on federal public debt interest services is an important factor that hinders the achievement of fiscal balance, as well as the country's economic growth. The evidence presented in the paper suggests that the achievement of a sustainable fiscal balance requires alteration of the current institutionality of public debt management, inherited from the period of high inflation, which, because of several rules of operation of the primary and secondary public debt markets discussed in the paper, interest rates converge to international standards. The fiscal cost of the institutional arrangement of the management of the brazilian public debt sums up the costs of the institutional complementarities built in the last decades with the monetary and exchange rate policy. These complementarities create a network of institutional arrangements with the attribute of path dependence, which makes it difficult to change in order to reduce these fiscal costs.
Keywords: B52; E43; E63; H62; H63; 330; fiscal imbalance; primary expenditure; public debt; interest service